Examining the Intergenerational Stake Hypothesis in Grandparent–Grandchild Dyads. (September 2019) - Spalding, Rachael; Carpenter, Brian
The intergenerational stake hypothesis posits that older people tend to feel more positively about their relationships with younger people in their family because they have a greater perceived "stake" in the relationship. Pairs of grandparents and grandchildren ( n = 79) completed a brief survey that asked questions about relational closeness, shared activities, and relationship quality. Both self- and proxy reports were gathered from each participant. On average, grandparents reported significantly more favorable self-reports of emotional closeness than their grandchildren. However, proxy reports revealed that grandparents were actually quite accurate at predicting their grandchildren's relational closeness responses. Moreover, difference score calculations identified a portion of the dyad sample (39 dyads) that appeared to refute the hypothesis in their relational closeness responses. Results from this study suggest that the generational stake phenomenon exists in the grandchild/grandparent relationship. However, the degree to which grandparents are aware of their grandchildren's perspectives may vary.